Gluten proteins: enzymatic modification, functional and therapeutic properties - Saadi, Sami; Saari, Nazamid; Mohd Ghazali, Hasanah; Abdulkarim, Sabo Mohammed; Abdul Hamid, Azizah; Anwar, Farooq (Elsevier, 2022)
Glutens are potential proteins with multifunctional therapeutic effects. Their covalence network structures with and without protease inhibitors are expected to enhance or to serve further properties and further technological points such as increased bioactive surfaces, gelatinization, gelation and pasting properties. The depletion of the allergic peptide sequences of gluten proteins comprising sometimes protease inhibitors are valid via the enzymatic ingestion using proteolytic enzymes that might enhance these functional and technological processes by producing active peptides having osmoregulation and regular glass transitions, surface activity for coating and encapsulation properties. In addition to further therapeutic functions such as immunoregulatory, antithrombin and opioidal activities, particularly in eradicating most of the free radicals, suppressing diabetes Mellitus II complications and inhibiting angiotensin converting enzyme cardiovascular growth diseases.